Proposta de metodologia para obtenção de índice global de produtividade em empreendimentos de construção civil - Maciel, Francisco Wandisley Freitas (2024)
Technical studies point out that civil construction has a lower productivity than other industries: while this sector has an increase of 1.0% per year, other sectors reach levels more than three times as high. In this conjecture, Brazil figures as a country that is "lagging behind", because it has shown low productivity and negative growth rates. The prolific studies in the area of civil construction management reveal that actions to improve the process and especially the measurement of productivity are a substantial challenge to this industry, especially because productivity is a potential influencer of costs and deadlines in projects. The literature has shown that labor productivity in civil construction in Brazil can vary between 20 and 80 man-hours/m². However, this indicator has the potential to lag easily, mainly due to the non-updating of data, the differences in the size of the companies and the different regional characteristics of the sample, i.e., measurement made in a certain region of the country, representing part of the industry. In addition, surveys tend to study indicators related to specific work packages and/or services, and not productivity in a global manner. Thus, the problem of this research relates to one of the main performance and management challenges in construction: productivity. Studies that present global results of project productivity, which means involving all construction processes in a global vision, from the beginning to the end of the work, are still incipient in Brazil. Thus, methods for calculating this type of index and its analysis are also deficient. The general objective of this work is to propose a model for measuring global labor productivity for real estate projects. The present research followed the Design Science Research methodology, whose proposal was to identify a practical problem and propose an artifact to solve it. The developed artifact is a theoretical model for measuring global labor productivity for completed and ongoing construction projects, which consists of eleven tools and aims to contribute to the measurement and communication of a global productivity indicator.